The Graham Volcanic Field Offshore Southwestern Sicily (Italy) Revealed by High-Resolution Seafloor Mapping and ROV Images - Cavallaro, Danilo; Coltelli, Mauro (Frontiers in Earth Science, 2019)
Using high-resolution bathymetric data and ROV images, the submarine Graham volcanic field, located 40-50 km offshore southwestern Sicily (Italy), has been characterized in detail. The field comprises a ten of monogenetic volcanic seamounts aligned along a N-S trending belt at 150-250 m water depths and includes the relict of the short-lived “Ferdinandea Island” produced during the well-documented 1831 “Surtseyan-type” eruption. The present-day morphology of the cones is the result of the interplay between volcanic activity, wave and current erosion, mass-wasting and depositional processes, in relationship with sea-level change, acting in both subaerial and submarine environments. The analysis of the morphometric parameters allowed a detailed morphological classification of the cones. The seamounts are composed of poorly consolidated tephra and show steep slopes and pointy or flat tops, often characterized by sub-vertical knolls. Taking into account analogies with other volcanic seamounts worldwide, the analysis of some morphological characteristics, such as presence and depth of terraces on top and along the slope of the cones in relationship with sea-level fluctuations, allowed us to hypothesize a Late Pleistocene-Holocene age for the volcanism forming the field. The probably older Terribile volcanic field was also identified on the adjacent Terribile Bank and analyzed. The distribution and shape of the cones within the volcanic fields provided important insights into the interaction between volcanism and tectonics. The alignment of the cones and the main axis of the clusters in which they were grouped, revealed two preferred directions, N-S and NW-SE, respectively, which are consistent with those of the main tectonic structures of the Sicily Channel. The detailed bathy-morphological analysis of the cones proved the monogenetic nature of this volcanism, which represents a peculiarity since it took place within a transfer zone outside the typical geodynamic settings of other volcanic fields such as subduction and rift zones, and far from long-lived volcanic systems. Finally, numerous mass transport deposits and pockmarks were identified in the surroundings of the volcanic fields, suggesting the occurrence of diffuse slope failures and fluid releases, respectively.